CO2 Gas Hydrate Promotion With Acetone Solution - Roslan, Hariz (IRC, 2015)
Impurities are common constituents in oil and gas production. One of the common impurity constituents is carbon dioxide. In South East Asia alone, gas reservoir regions are well known to have a CO2 content more than 0.7 mole fraction of the gas production. One of the methods of carbon capture is the cryogenic method, or by using gas hydrate promoter. In the study presented here, the experimental dissociation data for carbon dioxide-methane mixture (70/30 in mol%) in a quaternary mixture of carbon dioxide, methane, water, and acetone (CO2-CH4-H2O-C3H6O) are analyzed with four (4) different concentrations of acetone solution (1 mol %, 3 mol %, 5 mol %, and 7 mol %) at three (3) different pressures of 30, 40, and 50 Bar using the T-cycling method. Based on the experimental data, as hydrate dissociation point increases, the concentration of acetone required increases along the buildup of pressure. In addition, according to the analyzed results, the optimum concentrations for gas hydrate promotion lie above 0.05 mol% as pressure increases above 30 bar.